Effectiveness of breast-conserving surgery in patients with breast cancer - Dinara Amanzholova; Valentina Sirota (National Scientific Medical Center, 2019)
Contemporary diagnostics methods can suspect the presence of tumors in mammary gland of minimal size. The current world trend in the treatment of breast cancer, especially early breast cancer, is the use of organ conserving treatment as a method that improves patient's quality of life with preserving mammary glands. This study systematizes results of recent researches which studied long-term results of treatment after radical mastectomy and breast conserving surgery.